<Arte contemporânea > Rotas #2 </performatividades do artista> - Pereira, Lucas de Castro (2021)
This dissertation seeks to contribute with a reflection on the performativity of artists, taking it as a poetic procedure whose manifestation draws on communicational processes between the artist and the art system. It analyzes, in particular, the constitution of heteronyms and performative personas in works such as Marcelo do Campo (Dora Longo Bahia, 2006) and A coleção Duda Miranda [The Duda Miranda Collection] (Marilá Dardot and Matheus Rocha Pitta, 2007). It also explores accounts of experiences and relationships of affection that permeate the development of this investigation—based on the conception of artist-etc proposed by the artist and researcher Ricardo Basbaum—as well as artworks stemming from the propositions of Lucas Odarres, heteronym of the author of this research, namely: Os cadernos de Lucas Odarres [The Notebooks of Lucas Odarres], Mirante [Belvedere], Rotas #1 [Routes #1] and Rotas #2 [Routes #2]. The aim is to explore the artist's regimes of presence as a potential to deconstruct the place he occupies in the contemporary art system, reflecting on the ways in which his performativities are organized as an important vector for the repositioning of his relational sphere as acting subject in society. Christine Mello's extremities approach is employed as a conceptual vector for poetic interpretation and constitution. Through the concepts of deconstruction, contamination and sharing, we seek to provide tools both for the analysis of the research corpus, and for the reflections and confrontations present in the artistic productions created during the period in which this research was carried out. The theoretical structure is interdisciplinary, with a perspective of performativity anchored in studies by authors such as John Langshaw Austin, Judith Butler and Philipe Auslander. The notions of performative persona and performative self-writings are addressed from the studies of Ana Goldenstein Carvalhaes and Janaina Fontes Leite. The discussions about the art system are articulated around the notion of networked communication circuit, presented in the studies of Anne Cauquelin, and that of field and art system, proposed by Pierre Bourdieu and Maria Amélia Bulhões